VISIBILITAS TALI MULTIFILAMEN UNTUK BAHAN ALAT PENANGKAPAN IKAN PADA KEDALAMAN PERAIRAN YANG - Nofrizal Nofrizal (Fakultas Perikanan dan Kelautan, Universitas Riau, 2014)
Visibility of multivilament with the white, red, yellow and blue color wasobserved in the waters by underwater digital camera (Canon G11). Themultifilament 10 mm in diameter was tied at wire frame (1 x 1 m). The wire framewas shot in 1-5 meter water depth with the distance 0.5-2 meter by underwaterdigital camera. The underwater photograph result show that the visibility distancesof red and blue multifilament was 1 meter. However, the visibility distance ofwhite and yellow multifilament was 1.5 meters. Furthermore, the effect ofenvironment factors on the visibility distance of multifilament and monofilamentwere discussed in this paper.Keywords: Color, fishing gear, multifilament, visibility